Dissociative Electron Attachment From Vibrationally Excited Molecules in Nanosecond Repetitively Pulsed CO Discharges and Afterglows - Pietanza, Lucia Daniela; Colonna, Gianpiero; Capitelli, Mario (Frontiers in Chemistry, 2019)
Non-equilibrium vibrational distributions and electron energy distributions of CO in nanosecond repetitively pulsed (NRP) discharges and afterglows have been determined from a coupled solution of the time dependent Boltzmann equation for the electron energy distribution function (eedf) of free electrons and the master equations for the vibrational distribution function (vdf) of CO and the electronic excited states of CO and O and C atoms. Emphasis is given to the role of dissociative electron attachment (DEA) from vibrationally excited states in affecting the eedf and vdf under extreme conditions, i.e. an optically thick plasma with quenching processes involving the electronic excited states, populated by a sequence of discharge pulses and corresponding afterglows. In particular, the quenching process of the a3Π electronic state of CO determines a pumping of vibrational quanta in the ground state, which in turn largely modifies the CO vdf promoting the activation of DEA process. DEA rate coefficients have been obtained by using a complete set of vibrational (v) dependent cross sections through the 〖CO〗^- (X(_^2)Π ) channel and by using the experimental v=0 cross section of Rapp and Briglia, which should include the contribution of other 〖CO〗^- resonant states. The importance of the last contribution has been also estimated by using a scaling law to extend the v=0 cross section over all the vibrational ladder of CO. In particular, this mechanism becomes competitive with the other reactive channels for very short inter-pulse delay times, i.e. the t_id=1 μs, being less important for longer inter-pulse delay times, i.e. the t_id=25 μs.